Misdiagnosis of Chikungunya Virus Infection: Comparison of Old and Younger Adults. Issue 9 (6th August 2018) - Godaert, Lidvine; Bartholet, Seendy; Gazeuse, Yannick; Brouste, Yannick; Najioullah, Fatiha; Kanagaratnam, Lukshe; Césaire, Raymond; Fanon, Jean‐Luc; Dramé, Moustapha
Abstract : Objectives: To assess the frequency of diagnostic errors in older adults presenting to the emergency department (ED) with symptoms suggestive of Chikungunya virus infection (CVI) and to compare the rates of misdiagnosis of older and younger adults. Design: Cross‐sectional study performed in the University Hospitals of Martinique from retrospective cases. Setting: Emergency department. Participants: Individuals aged 65 and older who attended the ED and underwent reverse transcription polymerase chain reaction (RT‐PCR) testing for CVI between January and December 2014 (n=333, mean age 80±8) were considered eligible and were compared with a randomly selected sample of younger adults (< 65) (n=143, mean age 45±13). Measurements: Misdiagnosis rates. Results: The rate of misdiagnosis of CVI in the ED was 30.6% in individuals aged 65 and older and 6.3% in those younger than 65 (p<.001). The overdiagnosis rate was 9.0% in individuals aged 65 and older and 3.5% in those younger than 65 (p=.04). The underdiagnosis rate was significantly higher (p<.001) in individuals aged 65 and older (21.6%) than in those younger than 65 (2.8%). Conclusion: Misdiagnosis of CVI during an epidemic is statistically more frequent in older than younger adults because clinical presentation is often atypical in older adults. Specific diagnostic tools for older adults and better awareness of ED physicians of different presentations in different age groups could help to reduce the rate of misdiagnosis of CVI in the ED.